ANALISIS PERAN PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA DINAS KOPERASI DAN UKM PEMERINTAH KOTA MAKASSAR - Hendra Gunawan (Universitas Ichsan Sidenreng Rappang, 2024)
This study aims to analyze the role of career development on employee performance through job satisfaction at the Department of Cooperatives and SMEs of Makassar City Government. The study employed a quantitative approach using a survey method with employees as respondents. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The results show that career development has a positive effect on job satisfaction and employee performance. In addition, job satisfaction also has a positive effect on employee performance. The findings further reveal that job satisfaction acts as a mediating variable in the relationship between career development and employee performance. These results indicate that career development plays an important role in improving job satisfaction and employee performance in public organizations. Therefore, organizations need to manage career development systems effectively to enhance job satisfaction and improve employee performance.